Idealização do masculino e do feminino a partir dos processos de crimes passionais na cidade de Vitória (1890-1930) - Pádua, Silvia Amaral Pimenta de (2010)
This work is a result of an investigation examining the differences between men and women during the first Brazilian Republic (1890-1930) in Espírito Santo, more specifically Vitória and its surrounding neighbors. Idealizations of the male and female social roles were analyzed investigating judicial rulings and affidavits of both first hand and eyewitness accounts in such cases of Crimes of Passion. The outcomes suggest that domestic violence and its legitimization were supported to maintain the Capixabas’ hierarchal social structure. Social Representations were generated from principles both positive and negative, which in turn guided the social practices of the subjects as either acceptable or not acceptable. In some cases judicial rulings proved impartial even when such decisions broke with the values considered crucial to the social order of the time. Lastly, this work desires to contribute to the saving of local history as it relates contextually to its national partner by specifically considering the histories of Vitoria, Espírito Santo.